العوامل المؤثرة في نجاح تعليم اللغة العربية: Factors that Influence the Success of Teaching Arabic - Ronny Mahmuddin; Munira Munira (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This study aims to describe the factors that influence the success of teaching Arabic. This type of research is descriptive qualitative research using the library research method. The results of the study indicate that the determining factors that influence the success of teaching Arabic, namely: (1) determining teaching objectives which include teaching plans, teaching materials and evaluations; (2) a teacher who has a very urgent role; (3) teaching facilities; (4) students, taking into account the background and abilities of the students; and (5) teaching environment. These five factors are interrelated with each other in realizing the success of teaching Arabic.